2017
DOI: 10.4172/2161-0711.1000558
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Intimate Partner Violence (IPV) Among Pregnant Women Seeking Antenatal Care, Solomon Islands (2016)

Abstract: Introduction: Violence against women by partners during pregnancy is a major public health concern. As there is no studies done in the Solomon Islands to date on the prevalence of Intimate partner violence (IPV) specifically in the pregnant population, this study is aimed to understand the prevalence and characteristics of Intimate Partner Violence (IPV) among pregnant women seeking antenatal care, Solomon Islands (2016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…Almost half of the women in this study reported experiencing physical or emotional violence during their pregnancy. This is consistent with previous Solomon Islands studies, which have reported that up to 66% of women experience domestic violence from their intimate partner during pregnancy [23,64]. Some of the women attested that being bashed or kicked in the back, led to early births, a serious consequence of violence during pregnancy [23,[64][65][66][67].…”
Section: Overview Of Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Almost half of the women in this study reported experiencing physical or emotional violence during their pregnancy. This is consistent with previous Solomon Islands studies, which have reported that up to 66% of women experience domestic violence from their intimate partner during pregnancy [23,64]. Some of the women attested that being bashed or kicked in the back, led to early births, a serious consequence of violence during pregnancy [23,[64][65][66][67].…”
Section: Overview Of Findingssupporting
confidence: 90%
“…Some of the women attested that being bashed or kicked in the back, led to early births, a serious consequence of violence during pregnancy [23,[64][65][66][67]. Despite the legislation of the Family Protection Act to protect families and promote safety and community education by the Solomon Islands government [64,68], many of the women expressed a lack of social and community support, particularly in rural communities.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…The level of violence reported is consistent with the literature. A 2016 cross-sectional descriptive study of intimate partner violence among pregnant women seeking antenatal care in the Solomon Islands found that 56% of participants reported experiencing intimate partner violence in pregnancy, with a prevalence of emotional, sexual and physical abuse of 45%, 33% and 17%, respectively 24. Other studies have reported high rates of intimate partner violence, with the Solomon Islands Family Health and Safety Study finding 64% of women aged 15–49 who have ever been in a relationship reporting experiencing physical or sexual violence, or both 28.…”
Section: Discussionmentioning
confidence: 99%
“…17 There is also a further descriptive study examining pregnant women's experiences of intimatepartner violence. 24 These studies likely under-report the incidence of gender-based violence due to many victims of domestic violence commonly not disclosing the mechanism of their injuries, 25 or not seeking medical treatment, 25 and these studies do not address the impact of gender-based violence.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation